Improving the user experience of delayed baggage associated with air travels - An interaction design study on how to identify user pain points and design based on them. - Henriksson, Louise; Rehnberg, Annie (My University, 2020)
The project Improving the user experience of delayed baggage associated with air travels was conducted at the Interaction Design department at Chalmers University of Technology as a master’s thesis by Louise Henriksson and Annie Rehnberg. The project is a cooperation with SAS - Scandinavian Airline System. Today, a traveler must go through a long, time consuming, manual process when they notice that their baggage is delayed. This is something that contradicts SAS’ vision, which is that they want to make life easier for travelers in Scandinavia (SAS, 2019a). The fact that travelers themselves are the ones that have to report the delayed baggage, and not the other way around, is something that suggests that the responsibility lies on the traveler, thus creating a bad user experience. Therefore the purpose of this project is to research how the experience with delayed baggage at airports is today and how it can be improved by defining a set of guidelines. The aim was also to identify the travelers' pain points and see if negative emotions could be reversed, thus creating a rich experience. The research question for this project was: Based on user pain points, what design guidelines should be considered to improve the user experience for delayed baggage tracking and reporting, associated with air travels? The project followed the structure of a double diamond approach, containing methods which gathered both user insights and technical constraints. Two personality types emerged, one that wants information about the delay as soon as possible and one that wants to stay unaware during the flight but receive the information immediately after landing. The project resulted in a list of requirements, six pain points, an interactive prototype for a mobile app and a set of six guidelines. To confirm the guidelines, three sets of usability tests were performed. They revealed that, even when designing based on the guidelines, the traveler still experiences negative emotions when they find out about the delay. However, after continuing in the interface, they start to feel more in control and excited again. This implies the emotions were reversed and that the prototype could create a rich memorable experience.